Prevalence of chondromalacia patella according to patella type and patellofemoral geometry: a retrospective study - Dursun, Muhsin; Ozsahın, Murat; Altun, Guray (São Paulo Medical Journal, 2022)
BACKGROUND: The relationships between the morphometric structure of the patellofemoral joint, patella type and chondromalacia patella are still a matter of debate. OBJECTIVE: To identify the prevalence of chondromalacia patella by determining the patella type and making patellofemoral morphometric measurements. DESIGN AND SETTING: Retrospective cohort study in an orthopedics and traumatology clinic in Turkey, conducted between June 2017 and November 2019. METHODS: This study involved 562 knees of 522 patients with anterior knee pain (246 males and 316 females; mean age 46.59 years). The patients were grouped according to presence of chondromalacia patella (group I) or absence of chondromalacia patella (group II). The patella type, lateral trochlear inclination, medial trochlear inclination, trochlear angle, sulcus angle, patellar tilt and Insall-Salvati index were assessed. Group comparisons were made using chi-square tests or Student t tests. The r value was used to determine the magnitude of relationships between pairs of variables. RESULTS: Among the 562 knees evaluated, 265 (50.71%) presented type I patella, 195 (36.7%) type II, 100 (12.3%) type III and 2 (0.3%) type IV. Group I consisted of 448 knees and group II consisted of 114 knees. Significant differences were found between the groups in terms of age, gender, patella type and lateral inclination angles (P < 0.05). CONCLUSION: Detecting the patella type and making lateral inclination measurements in patients with anterior knee pain are of great importance for diagnosing suspected chondromalacia patella, particularly in the early degenerative period.